Epistemologi Kritisisme Royce sebagai Dasar Menentukan Ukuran Kebenaran - Soeprapto, Sri (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 1999)
Royce explains the meaning of idea as a representative of facts or as a idea which correspond with that facts. The facts were understood as external meanings of idea, whereas the essence as internal meaning of idea. The probelm of this research is how the relation between the concept of idea and the facts? and what is the criterion of the truth? The aim of this research are to systematize and to evaluate concept of Criticism which be promoted by Royce as a foundation to definite the criterion of the truth.The material object of this research are the books have been written by Royce and be supported by the books of researchers which have analyzed Royce's books. Dara collected by analyzed by interpretation, coherency intern, and comparative methods. Interpretation and intern coherency method are intended to systematize Criticism concept of Royce. Comparative method is used to evaluate and to compare Royce's concept with other Criticism concept.The result of this research appers that meaning of internal idea an intuitive knowledge about the ultimate, which have the highest truth. The intuitive knowledge is direct knowledge, so that its charactersitic is a potential truth until be examined by the others subject. The facts are external meaning which not the all of them can by systematized by the internal meaning of idea. The external meaning not automatically as a truth. The truth of knowledge about the objects is a process of systematicize the external meaning by the internal meaning of idea. Â